(untitled) (Journal of the College of Education for Women, 2019)
In The Bluest Eye (1970), the American-African writer, Toni Morrison explores howWestern standards of ideal beauty are created and propagated with and among the blackcommunity. The novel not only portrays the lives of those whose dark skinned and Negroidfeatures blight their lives; it also shows how the standard of white beauty, when imposed onblack youth, can drastically damage one’s self-love and esteem which usually occurs whenbeauty goes unrecognized. Morrison in this novel focuses on the damage that the blackwomen characters suffer through the construction of femininity in a racialised society wherewhiteness is used as a standard of beauty.